Efficacy of two diode lasers in the removal of calculus from the root surface: An in vitro study - Domenico Marcattili; Leonardo Mancini; Francesco Tarallo; Fabio Casalena; Carla Pietropaoli; Enrico Marchetti (Wiley, 2023)
Abstract Introduction Scaling and root planning (SRP) is still the gold standard of nonsurgical periodontal therapy, and it has been accompanied by several supportive therapies in recent years. One of the most studied methods is the diode laser, thanks to its thermal and bactericidal properties. Our trial intended to verify whether it could influence the chemical bond between calculus and the root surface. Objectives The aim of the study was to assess the efficacy of the diode laser prior the mechanical removal of calculus in an in vitro application. The reduction in time and the number of strokes required to clean the untreated root surfaces were evaluated as primary outcomes. The pressure was considered as a secondary outcome. Methods A total of 75 extracted human teeth with subgingival calculus were assigned equally among three treatment groups (n = 25) according to the size of the occupied areas, which were classified by evaluating the pixel numbers. The groups were assigned to either no pretreatment application (A), Laser Diode Fox III (Sweden & Martina) (B) or Wiser Laser Evolution (Doctor Smile) (C). The weight for instrumentation was calibrated for an After Five curette (Hu‐Friedy, Chicago). A new set of tools was used for each group, and the curettes were sharpened after each use with the Sidekick sharpener (Hu‐Friedy, Chicago). Results A Kruskal-Wallis test was used to assess the significance for each considered parameter. The results were statistically significant for each parameter for the two groups where the laser was used compared to the control group. Conclusions Despite the limitations of an in vitro study, data showed that the diode laser had an overall positive effect on root debridement, facilitating SRP in terms of stroke count, time, and pressure.